Um máximo empírico para a esfericidade de vetores aleatórios : aplicação ao crescimento somático de ratos em um estudo com modelo experimental de hipotireoidismo gestacional - Santana, Demetrius Silva de (2017)
Hypothyroidism, in both its clinical and subclinical manifestations, is a highly prevalent endocrinopathy among pregnant women. Given the high fetal dependency on maternal thyroid hormones (TH), a shortage of these hormones can be related to long-term effects on organisms, as TH have ubiquitous actions. Particularly, effects of gestational hypothyroidism on kidneys could cause an elevation of blood pressure later in life. An indicator of fetal programming can be the somatic growth of an organism, which, in rats, is hard to be modelled due to persistent growth post-puberty. With this purpose, use of body weight in analysis of variance (ANOVA), taking animal age as repeated measures factor (RMF), can cause nonsphericity in this statistical model. A goal was to evaluate, on adult offspring, the influence of maternal TH deficiency on renal function and on somatic growth, as well the relationship between renal function and systolic arterial pressure (SAP). Additionally, we sought an adequate method of analysis for body weight curves of rats and investigated consequences of using ANOVA as usual for this purpose. Female Wistar rats were divided in three main experimental groups: control euthyroid; hypothyroid by addition of methimazole (0.02%) in drinking water; and euthyroid by hormonal replacement, receiving both methimazole (0.02%) and levothyroxine (T4, 100 μg/L) in drinking water. Treatment was given between gestational days (GD) 9 and 21. On offspring, either nephrectomy or sham-surgery was done at post-coitus day (PCD) 26. Blood pressure was evaluated at around postnatal day (PND) 90, through a tail-plethysmograph. Blood and urine were collected at around PND 110 to evaluate creatinine clearance. To evaluate somatic growth, animals were weighed once to thrice weekly after weaning. Analysis of weight data was done by fitting a modified tetraparametric sigmoid curve to weight data and reducing its parameters by principal component analysis, whereby two principal components were able to retain 92% of original variance of parameters. Experimental gestational hypothyroidism (EGH) had no effect on SAP (p* > 0,200), except through its interaction with estrous cycle. There was a third order interaction concerning estrous phase, nephrectomy and T4 replacement, where the luteal SAP drop was intensified (p* = 0,039). Body weight at PCD 26 did not show any correlation with SAP (p* = 0,716). There was no correlation between SAP and creatinine clearance (p* = 0,803). EGH had no significant effect on creatinine clearance nor on weight curve principal components (p* > 0,200). Thus, given current approach, it was not possible to detect any EGH effect on SAP, neither on renal function, nor on somatic growth. Analysis of body weight curves allowed a precise definition of the beginning of adulthood of animals regarding their somatic growth and elaboration of a simplified model of somatic growth of rats. Also, it was possible to establish an empirical maximum for the coefficient of sphericity of studies which use repeated measures ANOVA to model continuous variables which have been discretized and used as RMF; this can be useful for both experimental planning and previous results reevaluation.